Livin Regulates H2A.XY142 Phosphorylation and Promotes Autophagy in Colon Cancer Cells via a Novel Kinase Activity - Ge, Yang; Liu, Bao-lin; Cui, Jun-peng; Li, Shu-qiang (Frontiers in Oncology, 2019)
Objective: To investigate Livin-mediated regulation of H2A.XY142 phosphorylation via a novel kinase activity and its effect on autophagy in colon cancer cells. Methods: The interaction between Livin and H2A.X was tested by immunoprecipitation. H2A.X-/- HCT116 cells were transfected with human influenza hemagglutinin (HA)-tagged WT or Y142F phospho-dead mutantH2A.X plasmids. GST-tagged recombinant Livin protein was used to perform in vitro pull-down experiment and kinase assay. H2A.X-/-Livin+/+ SW480 cells were co-transfected with H2A.XWT/H2A.XY142F plasmid and LC3 EGFP-tagged plasmid to explore whether H2A.XY142F was involved in Livin-mediated autophagy induced by starvation in colon cancer cells. Results: Co-immunoprecipitation studies confirmed that Livin interacted with H2A.X and that it was phosphorylation dependent. In vitro kinase assay confirmed that Livin could phosphorylate H2A.X. Knockdown of Livin (Livin-/-) in SW480 cells or HCT116 cells cancelled the starvation-induced autophagy in colon cancer cells; H2A.X-/-Livin+/+ SW480 cells transfected with H2A.XWT activated autophagy induced by starvation while cells transfected with H2A.XY142F had no significant difference; Livin-H2A.XY142F axis activated autophagy in colon cancer cells through transcriptionally regulating ATG5 and ATG7. Conclusion: Livin promotes autophagy in colon cancer cells via regulating the phosphorylation of H2A.XY142.